Landscape Context Affects Aphid Parasitism by Lysiphlebus testaceipes (Hymenoptera: Aphidiinae) in Wheat Fields. Issue 4 (12th April 2018) - Elliott, Norman C; Brewer, Michael J; Giles, Kristopher L
Abstract: Winter wheat is Oklahoma's most widely grown crop, and is planted during September and October, grows from fall through spring, and is harvested in June. Winter wheat fields are typically interspersed in a mosaic of habitats in other uses, and we hypothesized that the spatial and temporal composition and configuration of landscape elements, which contribute to agroecosystem diversity also influence biological control of common aphid pests. The parasitoid Lysiphlebus testaceipes (Cresson; Hymenoptera: Aphidiinae) is highly effective at reducing aphid populations in wheat in Oklahoma, and though a great deal is known about the biology and ecology of L. testaceipes, there are gaps in knowledge that limit predicting when and where it will be effective at controlling aphid infestations in wheat. Our objective was to determine the influence of landscape structure on parasitism of cereal aphids by L. testaceipes in wheat fields early in the growing season when aphid and parasitoid colonization occurs and later in the growing season when aphid and parasitoid populations are established in wheat fields. Seventy fields were studied during the three growing seasons. Significant correlations between parasitism by L. testaceipes and landscape variables existed for patch density, fractal dimension, Shannon's patch diversity index, percent wheat, percent summer crops, and percent wooded land. Correlations between parasitism and landscape variables were generally greatest at a 3.2 km radius surrounding the wheat field. Correlations between parasitism and landscape variables that would be expected to increase with increasing landscape diversity were usually positive. Subsequent regression models for L. testaceipes parasitism in wheat fields in autumn and spring showed that landscape variables influenced parasitism and indicated that parasitism increased with increasing landscape diversity. Overall, results indicate that L. testaceipes utilizes multiple habitats throughout the year depending on their availability and acceptability, and frequently disperses among habitats. Colonization of wheat fields by L. testaceipes in autumn appears to be enhanced by proximity to fields of summer crops and semi-natural habitats other than grasslands.